Effect of Teachers’ Health Behaviors on Students’ Health; A Social Cognitive Viewpoint of Role-Modeling - Aryal, Bhagwan (Interdisciplinary Research in Education, 2022)
Teachers as role models teach and set an example through their actions. Students routinely observe and are directly influenced by the teacher's health behavior. Unfortunately, school teachers are vulnerable to many health issues that affect student success. Teachers are often absent, showing examples of poor health. This study sought information on the impact of teachers' health behaviors on student health from a cross-sectional descriptive study of mixed methods in secondary schools of Bagmati Province, Nepal. The total sample size of the students in the quantitative interview was 412 from 46 randomly selected schools in the Rasuwa, Bhaktapur, and Chitwan districts. Another 30 students from different schools were selected for in-depth study. It focused on finding out how students identify teachers as role models. Since the concept of role models appears in Albert Bandura's social learning/cognitive theory, which focuses on cognitive concepts, this study examined student cognition to connect to the role modeling structure of the theory. This theory focuses on how children and adults cognitively process social experiences and how these cognitions affect behavior and development. In the light of this theory, it was explained the effect of teacher health behaviors on student's health. Observable health behaviors of teachers are proved to have positive and negative impacts on students' health.